(untitled) (Raparin Journal of Humanities (RJH), 2024)
Civilization and history are two autonomous notions while there is an important correlation between them. We are not able to say anything on civilization without looking back at history. One can say civilization creates history and history rewrites civilization. It is the duty of history to explore and study civilization and the reason for their creation thoroughly. According to Spengler’s analysis the interpterion of civilization and history in his famous book (The decline of the West). He believes that the principal of history is civilizations. History is inconceivable in its true meaning, without civilization. He mentions that each civilization has its own figures. This philosopher believes that like all the other creatures civilization is born and alive and passes through all stage of live, youth, old ages and death. Which is a current role of history. Conversely, Ibn Khaldun considers that history is a science among the sciences, it has its own methods that the historical events can be clarified historically and each accident can be attributed to its actual intention. The historians must use different methods. They must have a critical idea. He believes that human society is developing just like an alive creature. Whenever a society becomes historic, another society takes its place. This cycle goes through several stages, migration stage, invasion stage and urban stage. Consequently, these theorists have an alive cycle analysis for the stages of civilization. They believe that as human beings civilization are born they grow and then they breakdown. Nonetheless, they have different opinions, Spengler claims that history isn’t a science. Conversely Ibn Khaldun has tried hard to identify history as a science. According to Ibn Khaldun, the nations are trying to improve life from migration to civilization. But then again according to Spengler the nations are basically belong to the civilization.